2019
DOI: 10.1051/0004-6361/201833010
|View full text |Cite
|
Sign up to set email alerts
|

The progenitors of type-Ia supernovae in semidetached binaries with red giant donors

Abstract: Context. The companions of the exploding carbon-oxygen white dwarfs (CO WDs) for producing type Ia supernovae (SNe Ia) are still not conclusively confirmed. A red-giant (RG) star has been suggested to be the mass donor of the exploding WD, named as the symbiotic channel. However, previous studies on the this channel gave a relatively low rate of SNe Ia. Aims. We aim to systematically investigate the parameter space, Galactic rates and delay time distributions of SNe Ia from the symbiotic channel by employing a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 99 publications
0
13
0
Order By: Relevance
“…Li & van den Heuvel 1997;Han & Podsiadlowski 2004;Tauris et al 2013), the present work enlarges the initial parameter regions of WD+RG systems forming WDs with M Ch , especially the initial parameter region in this work containing more massive RG donors. The main reason is that the present work adopted an adiabatic power-law assumptions for the mass-transfer process, which is more reasonable for semidetached binaries with RG donors (see also Liu et al 2019).…”
Section: Comparison To Previous Studiesmentioning
confidence: 99%
“…Li & van den Heuvel 1997;Han & Podsiadlowski 2004;Tauris et al 2013), the present work enlarges the initial parameter regions of WD+RG systems forming WDs with M Ch , especially the initial parameter region in this work containing more massive RG donors. The main reason is that the present work adopted an adiabatic power-law assumptions for the mass-transfer process, which is more reasonable for semidetached binaries with RG donors (see also Liu et al 2019).…”
Section: Comparison To Previous Studiesmentioning
confidence: 99%
“…By adopting a power-law adiabatic supposition for the mass-transfer prescription that can be well applicable for the mass-transfer process from a RG donor (e.g., Ge et al 2010 recently enlarged the parameter space of WD+RG systems for producing WDs with M Ch . It seems that the adiabatic mass-transfer prescription for RG donor is still highly uncertain (e.g., Woods & Ivanova 2011), but the work by Liu et al (2019) at least provides an upper limit for the parameter regions that can form WDs with M Ch . Fig.…”
Section: Parameter Space For Aic Eventsmentioning
confidence: 99%
“…Claeys et al (2014) and Wang et al (2015) simulated the CO WD and main sequence star (CO WD+MS) channel, and found most of the SNe Ia are produced in 10 8 ∼ 10 9 years after star formation. Liu et al (2019) simulated the CO WD and red giant star (CO WD+RG) channel, and found the delay time to be 10 8.6 ∼ 10 8.7 years but with a steeper delay time relation than that of the DD scenario. Apart from MS or RG serving as the companion star, Wang et al (2017) simulated CO WD + He star as SN Ia progenitor system, which shows a peak of the event rate around 10 8 years.…”
Section: Introductionmentioning
confidence: 99%